Lipid Status During Combined Treatment in Prostate Cancer Patients. Issue 5 (October 2019) - Wolny-Rokicka, Edyta; Tukiendorf, Andrzej; Wydmański, Jerzy; Ostrowska, Małgorzata; Zembroń-Łacny, Agnieszka
The aim of this study was to provide a specific review of current medical literature regarding the lipid profile during prostate carcinoma (PCa) treatment. The main aim was to analyze the results presented by different authors and to find a commonality in the changes occurring during the treatment—hormonotherapy. The levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL) cholesterol, and low-density lipoprotein (LDL) cholesterol were measured before and after the follow-up treatment. The manuscripts reviewed came from the period between 2008 and 2016. The size of the studies ranged from 16 participants to 310. The mean age was from 65 to 74 years in all studies. The Q test was used to attain all lipid parameters and to specify heterogeneity ( p < .0001). After 12 months of androgen deprivation therapy (ADT), the patients had a significantly higher level serum TC and TG.